Recent advances in linearly polarized emission from organic light-emitting diodes - Ding, Ran; Ye, Gao-Da; Feng, Jing (Applied physics letters, 2023)
Since the first example of linearly polarized organic light-emitting diodes (LP-OLEDs) reported by Dyreklev et al. [Adv. Mater. 7, 43 (1995)], remarkable efforts have been devoted to the development of LP-OLEDs, particularly in recent years. LP-OLEDs, as a next-generation light source, have attracted increasing interest for their capability of directly generating linearly polarized light as well as for their wide potential applicability in optical data storage, high-contrast display, and three-dimensional (3D) imaging. In this review, we systematically summarize the recent advances in LP-OLEDs that are roughly divided into three categories, including mechanical treatment, structural assistance, and self-assembled materials. This review is expected to provide an updated and impressive perspective on high efficiency and high polarization LP-OLEDs for a broad range of scientists in a multi-disciplinary field and draw more attention to this growing research field.